Enhanced electrochemical performance of fumed silica-based gel electrolyte with polypyrrole for valve-regulated lead-acid batteries - Mira, Ziyad; Turu, Irem Cemre; Gencten, Metin (SPRINGER, 2025)
In this study, chemically synthesized polypyrrole, a conductive polymer, was introduced for the first time to enhance the electrical conductivity and charge transfer characteristics of fumed silica-based gel electrolytes in valve-regulated lead-acid batteries. The optimization of key parameters-polypyrrole content, agitation time, and stirring rate-was carried out using electrochemical techniques, including cyclic voltammetry, electrochemical impedance spectroscopy, and Tafel polarization. The optimal performance of the gel system was achieved with 0.8 wt% polypyrrole, 60 min of agitation time, and a stirring rate of 500 rpm. Battery performance was evaluated through charge-discharge tests at a current density of 5 mA g(-)1. The polypyrrole gel electrolyte exhibited a specific capacity of (50.98 mAh g(-)1), superior to the fumed silica gel (44.01 mAh g(-)1) and sulfuric acid (18.83 mAh g(-)1) electrolytes. Long-term cycling tests at 7 mA g(-)1 revealed an 86% capacity retention after 100 cycles, indicating excellent stability. Even after 1000 cycles, a capacity retention of 67% was maintained, demonstrating good long-term durability. The enhancement in performance was attributed to the increased electrical conductivity and reduced charge transfer resistance due to polypyrrole addition. These results demonstrated the potential of polypyrrole to improve valve regulated lead acid battery performance, offering better efficiency and longevity for energy storage applications.
Keywords: Polypyrrole additive; Polypyrrole-doped gel electrolyte; Gel electrolyte optimization; Fumed silica-based gel electrolyte; CONDUCTING POLYMERS; ENERGY-STORAGE; CARBON; SULFATION; Electrochemistry